A Triad of Congenital Diaphragmatic Hernia, Meckel's Diverticulum, and Heterotopic Pancreas - Parkash Mandhan; Amer Al Saied; Mansour J. Ali (Hindawi Limited, 2014)
Congenital diaphragmatic hernia is a common developmental anomaly encountered by paediatric surgeons. It is known to be associated with extradiaphragmatic malformations, which include cardiac, renal, genital, and chromosomal abnormalities. Herein, we report a newborn born with concurrent congenital diaphragmatic hernia, Meckel's diverticulum, and heterotopic pancreatic tissue. This is the first case report of such a triad with description of possible mechanisms of the development.